Increasing the efficiency of burning low-reactive coal in vortex burners of boilers with dust supply with a high concentration under pressure - Kesova L.O.; Kravchuk G.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2017)
In the EU, USA, and a series of developed countries of the world, the ash and slag of power plants are considered as technogenic raw materials for many branches of industry. The systems of pneumatic ash and slag removal are an integral part of the technological process of coal-fired power plants and usually provide up to 92% of their utilization. In Ukraine, the systems of hydraulic ash and slag removal are applied, and, as a consequence, ash and slag lose their consumer value for using in industry. In addition, their accumulation in ash dumps leads to land allotment problems, the pollution of soil, ponds, and atmosphere, the dust loading of territories, and the possibility of catastrophic breakthrough of dams. We give recommendations for Ukrainian power plants regarding the choice of equipment and technologies for dry methods of ash and slag removal, which have obtained a positive verification in the world.